Intensive System of Whiteleg Shrimp (Litopenaeus vannamei Boone, 1931) Enlargement Technique at High Salinity - Akbarurrasyid, Muhammad; Sofiyani, Mauliza; Zainul Arifin, Irvan Firman Syah; Sudinno, Dinno; Astiyani, Wahyu Puji (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
White leg shrimp (Litopenaeus vannamei) rearing is an activity to produce shrimp in a certain amount. L. vannamei production is carried out using an intensive system method by considering good fish cultivation practices (CBIB) and water quality factors such as salinity. This study aims to determine the L. vannamei rearing technique at high salinity. The study was conducted using the ex post facto causal method in ponds in the Sukabumi area, West Java. The rearing activities carried out include: pond preparation, sterilization and water formation, seed distribution, maintenance, growth monitoring and harvesting and post-harvesting. The results of monitoring the growth of L. vannamei cultivated with high salinity showed that the Average Body Weight (ABW) value ranged from 1,56-25,14 g/individual (T1) and ranged from 2,1-23,98 g/individual (T2). The Average Daily Growth (ADG) value of T1 ranged from 0,04-0,65 g/day and T2 ranged from 0,06-0,53 g/day. Meanwhile, the Survival Rate (SR) value obtained is included in the high category, namely: 90,15% (T1) and 85,91% (T2). The results of water quality observations during the maintenance period are included in the optimal category according to growth requirements. Cultivation of L. vannamei with high salinity can increase growth rate and survival and optimize water quality.